EVALUASI PERMASALAHAN GAS INTERFERENCE PADA ELECTRICAL SUBMERSIBLE PUMP DI SUMUR MD-17 - Hermawan, Bagus Danial; Welayaturromadhona, Welayaturromadhona; Saputri, Eriska Eklezia Dwi; Sari, Riska Laksmita; Abror, Hadziqul (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2023)
Natural flow can not be performed in the reservoir from the MD-17 well. The most likely reason is because it is classified as a mature well, so an Artificial Lift is needed. The artificial lifting mechanism used is the Electrical Submersible Pump. In this research, the writer analyze the problem of